THE CHALLENGES POSED BY AI-GENERATED MISINFORMATION IN THE MEDIA AND ITS POTENTIAL EFFECTS ON LEGAL PROCEEDINGS - Anjum Saxena, (Chelonian Research Foundation, 2024)
As artificial intelligence (AI) technologies advance, the generation of misinformation has become increasingly sophisticated and pervasive within electronic media. This paper examines the challenges posed by AI-generated misinformation and its potential effects on legal proceedings. AI systems, particularly those utilizing deep learning techniques, can create hyper-realistic content, including text, images, and videos that misrepresent facts or fabricate events. Such misinformation can lead to significant public misperception regarding ongoing legal cases, potentially influencing jury pools and public opinion. The paper explores several dimensions of this issue, including the mechanisms through which AI-generated misinformation spreads, the role of social media platforms in amplifying these false narratives, and the psychological impact on audiences. Furthermore, it discusses how this misinformation can interfere with the right to a fair trial, compromising the integrity of legal proceedings. Specifically, we analyze cases where juror bias has been exacerbated by misleading media portrayals, leading to unjust outcomes. Moreover, the research delves into the legal implications of misinformation, addressing the challenges faced by courts in distinguishing between authentic and fabricated evidence. The paper also considers the responsibilities of media organizations and technology companies in mitigating the dissemination of AI-generated misinformation and the potential need for new regulatory frameworks. Ultimately, this paper aims to raise awareness about the intersection of AI, media, and the judiciary, emphasizing the urgent need for strategies to combat misinformation. By fostering a deeper understanding of these challenges, stakeholders can better safeguard the integrity of the legal system in an increasingly digital age.